Lateral Spreading in Christchurch, New Zealand: An Empirical Approach - Ultari, Megah (Universitas Negeri Padang, 2024)
Lateral spreading, a complex phenomenon resulting from liquefaction, manifests when saturated, cohesionless soils lose their strength during seismic events, causing them to deform and flow horizontally. This process poses a substantial risk to buildings and infrastructure, often resulting in extensive damage, significant financial burdens, and, tragically, loss of life. In Indonesian, liquefaction is recognized for its ability to transform solid ground into a fluid-like state, amplifying its danger in regions prone to earthquakes. This study aims to analyze lateral spreading through empirical methods, specifically employing the Bartlett & Youd Method (2002) and the Byrne Method (1990). The analysis focuses on sites previously affected by lateral spreading, notably those impacted by the 22 February 2011 Christchurch earthquake, which registered a magnitude of 6.2 and a peak ground acceleration of 0.52. The selected locations include the South Brighton Bridge, Anzac Bridge, and Fitzgerald Bridge in Christchurch, New Zealand. The findings demonstrate that both the Bartlett & Youd Method (2002) and the Byrne Method (1990) yield results that closely approximate the actual conditions at site.